2012
DOI: 10.1093/humrep/des329
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for genetic association with the let-7 microRNA-binding site or other common KRAS variants in risk of endometriosis

Abstract: STUDY QUESTIONIs there a contribution of the minor allele at the KRAS single nucleotide polymorphism (SNP) rs61764370 in the let-7 microRNA-binding site to endometriosis risk?SUMMARY ANSWERWe found no evidence for association between endometriosis risk and rs61764370 or any other SNPs in KRAS.WHAT IS KNOWN ALREADYThe rs61764370 SNP in the 3′ untranslated region of the KRAS gene is predicted to disrupt a complementary binding site (LCS6) for the let-7 microRNA, and was recently reported to be at a high frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In women harboring this KRAS variant, altered miRNA binding leads to increased proliferation of endometrial stroma cells, invasion, abnormal endometrial growth and finally endometriosis . However, these results were not replicated in a much larger study, without finding a large difference between cases and controls allele frequency . It was recently demonstrated that decreased H19 lncRNA in the endometrium of endometriotic women increases let‐7 miRNA activity, which in turn inhibits Igf1r expression at the post‐transcriptional level.…”
Section: Epigenetics Of Endometriosismentioning
confidence: 99%
“…In women harboring this KRAS variant, altered miRNA binding leads to increased proliferation of endometrial stroma cells, invasion, abnormal endometrial growth and finally endometriosis . However, these results were not replicated in a much larger study, without finding a large difference between cases and controls allele frequency . It was recently demonstrated that decreased H19 lncRNA in the endometrium of endometriotic women increases let‐7 miRNA activity, which in turn inhibits Igf1r expression at the post‐transcriptional level.…”
Section: Epigenetics Of Endometriosismentioning
confidence: 99%
“…SNP rs61764370 interrupts the link between the LCS6 complementary site and let-7 miRNA, altering the expression of the KRAS gene and favouring the development of the disease. The analysis conducted in 2012 by Hien Luong and Painter denied this risk association [73]. A meta-analysis of the GWASs of the IEC and the Japanese group, carried out in 2012, confirmed the associations previously reported in the respective studies and identified further significant new loci of association localized on GREB1 genes, involved in estrogenic regulation; VEZT, involved in cell growth, migration and adhesion; and ID4, an ovarian tumour suppressor [17].…”
Section: Genes Related To the Process Of Dna Repairmentioning
confidence: 76%
“…Based on genome-wide association study, the same finding was reported by a European report. 16 In addition to geographical variations, other contributing factors such as probable somatic alteration of KRAS LCS6 SNP in endometriosis tissue, help explain the controversy.…”
Section: Discussionmentioning
confidence: 99%